Pengaruh Metode Konseling terhadap Pengetahuan dan Sikap tentang Vaksinasi Human Papilloma Virus (HPV) - Desi Br Sembiring (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2022)
Prevention of cervical cancer will be more effective if it is carried out together with the provision of HPV vaccination as a specific protection effort. Ninety-five percent of the causes of cervical cancer come from the environment in the form of Human Papilloma Virus (HPV) and the other 5% are hereditary. Objective: To determine the effect of counseling method on knowledge and attitudes regarding HPV vaccination among adolescent girls. This was a Quasi Experimental study using pre-test and posttest with control group design. The sampling technique applied here was simple random sampling. The sample consisted of 25 respondents in the experimental groupwith counseling and 25 respondents in the control group with lecture. The research was conducted from June to August 2019. Data analysis used Paired t-test, Independent sample t-test and Manova. The mean increase in knowledge in the experimental group was 54.92 with a p-value of <0.0001. Furthermore, the mean increase in knowledge in the control group was 38.60 with a p-value of <0.0001. The mean increase in attitude in the experimental group was 45.40 p-value of <0.0001 and the mean increase in attitude in the control group was 34.16 with a p-value of <0.0001. The difference in knowledge in the experimental group was 84.15 and the difference in the control group was 68.55 with a significant level of <0.0001. The difference in attitude in the experimental group was 84.38 and the difference in the control group was 72.45 with a significant level of <0.0001. Counseling method had a significant effect on knowledge and attitudes regarding HPV vaccination among adolescent girls.